Stakeholders Collaboration in Empowering Coastal Communities - Darmi Titi (EDP Sciences, 2021)
Community empowerment has been reported to lead to societal dependence, as symptoms tend to allow the population not to be independent. In the coastal area of Bengkulu City, community empowerment has been reported to be carried out, most especially among the fishing population. However, it was not conducted sustainably, resulting in independence for the fishing community. For example, several Agencies often assist with temporary benefits. Moreover, there is no evaluation of program outcomes, as the assistance services do not run optimally. This study aims to describe the stakeholder collaboration patterns in empowering the coastal community at Bengkulu city. The method used was descriptive qualitative, as data were collected through observations, interviews, and documentation. The determination of objects was also carried out via the use of purposive and convenience sampling techniques. Also, the triangulation technique was used in order to check the data validity. The results showed that stakeholder collaboration was not being efficient and effective. The indicators also showed that the involved stakeholders have not entered into agreements and cooperation, which were observed as an effort to increase the capacity of coastal communities.